Correlation of Nutrition Education Model for Pregnant Women In Industrial Areas To Increase Knowledge of Nutrition, Nutritional Behavior, and Hemoglobin Levels of Pregnant Women - Lasiyati Yuswo Yani; Raras Merbawani; Asef Wildan Munfadlila (Universitas STRADA Indonesia, 2020)
Mojokerto is an industrial city which accounts for as much as 40% of the total female employees of reproductive age in the East Java region. The health status of pregnant women in industrial areas is something that must be considered in order to produce a superior Indonesian generation. The research design used the